Gray-Scale Image Compression Method Based on a Pixel-Based Adaptive Technique - Abed, Zahraa.H.; AL-Khafaji, Ghadah K. (Iraqi Journal of Science, 2024)
Today in the digital realm, where images constitute the massive resource of the social media base but unfortunately suffer from two issues of size and transmission, compression is the ideal solution. Pixel base techniques are one of the modern spatially optimized modeling techniques of deterministic and probabilistic bases that imply mean, index, and residual. This paper introduces adaptive pixel-based coding techniques for the probabilistic part of a lossy scheme by incorporating the MMSA of the C321 base along with the utilization of the deterministic part losslessly. The tested results achieved higher size reduction performance compared to the traditional pixel-based techniques and the standard JPEG by about 40% and 50%, respectively, with pleasing quality exceeding 45 dB.